The Rise of the Underground: Moroccan Music festivals between Laughter, Drunkenness, and Excre-Mentality - Maarouf, Moulay Driss El (Academic Quarter | Akademisk kvarter, 2011)
The same act of reaching across social boundaries is discussed in Moulay Driss El Maarouf’s article The Rise of the Underground where he develops what he refers to as the politics of excrementality; a way to articulate ways of resistance through dirty-mindedness. The music festival, in this case specifically Morocco but conceivably at work everywhere, with its carnivalesque mood becomes a site for vulgar and profane performances not simply from the musicians themselves but from the participants of the festival, which may then engender a community of transgression.